HUBUNGAN TINGKAT PENDAPATAN KELUARGA DENGAN STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS KALIJAMBE - Handini, Dian; Ichsan, Burhannudin; Nirlawati, Dona Dewi (Biomedika, 2013)
The state of nutritional status of children in Central Java based on index of height for age data obtained 16.9% of children who have growth in a very short, short 17.0% of infants and 66.1% of normal infants. Economic growth in Sragen in 2000 was 2.85%, decreased in 2001 to 2.26%, and increased in 2002-2003, respectively 2.93% and 3.26%. Research methode was observational cross sectional analytic approach. The number of samples was 65 toddlers. Data analysis using Chi Square. The nutritional status of children by index weight for age (W/A) were experiencing malnutrition while the remaining 13.8% as having good nutrition as much as 86.2%, and the index based on height for age (H/A) which had malnutrition as much as 46.2% while the rest had good nutrition as much as 53.8%, while the index by weight according to height (W/H) were experiencing malnutrition while the remaining 13.8% as having good nutrition as much as 86.2% . The results of the analysis obtained p count is 0.009 to the sample distribution based on W/A, and 0.010 for sample distribution based H/A, and 0.009 for the distribution of the sample by W/H. There is a relationship between the level of family income to the nutritional status of children in the working area Public Health Center Kalijambe.Keywords: Family Income, Nutritional Status of Children